Standardization of novel technique for preparation of ginger (Zingiber officinale)-blended wine from different cultivars of pear (Pyrus communis) - ATTRI, B L; KUMAR, ANIL; MER, MUKESH SINGH; KISHOR, ARUN (The Indian Journal of Agricultural Sciences, 2017)
In North-West Himalayas including Kumaon region of Uttarakhand pear (Pyrus communis L.) cultivars like Jagner, Sand Pear and Kakria are being grown with very high yield and productivity but due to poor market the growers are reluctant to harvest the crop because of which the nutritious fruits are spoiled in the orchards. Except for Jagner which is soft and used for table purpose, there are very few takers for other cultivars like Sand Pear and Kakria. All the cultivars are rich in various phyto-chemical characters including anti-oxidants. Hence, for reducing the huge spoilage of nutritious fruits, an attempt was made to standardize a novel technique for pear wine from three cultivars after blending their juice with 2.5% ginger (Zingiber officinale Roc) juice, 0.1% DAHP and 0.2% pectinol. After complete fermentation with yeast, Saccharomyces cerevisiae var. ellipsoideus, the prepared base wines were siphoned/filtered at regular intervals and stored at ambient conditions. A significant difference was recorded in bio-chemical and sensory quality attributes of the wines after preparation and 6 months storage. Among all the treatments ginger-blended Sand Pear wine prepared by raising the TSS to 22oB and having 2.5% ginger juice had an edge over other treatments in overall quality. A significant reduction in all the parameters was recorded irrespective of the cultivars used for wine preparation. On the basis of the study the cost of production of ginger-blended pear wine was found quite reasonable (Rupees 93.10, 73.10 and 73.10/650 ml bottle for Jagner-ginger, Sand Pear-ginger and Kakria-ginger wines respectively) with good profit margin comparable with low alcoholic beverages available in the market.